Herbal Simples Approved for Modern Uses of Cure - Fernie, William Thomas, 1830- (Salt Lake City, UT : Project Gutenberg, 2006)
"Herbal Simples Approved for Modern Uses of Cure" by William Thomas Fernie is a scientific publication written in the late 19th century. This text focuses on the medicinal properties of various herbs, providing detailed explanations and justifications for their use as healing remedies in contemporary medicine. Fernie guides readers through the historical use of herbal medicine while anchoring his insights in modern chemical analysis, thus reconciling traditional practices with contemporary scientific understanding. The beginning of the book introduces the concept of "Herbal Simples," defined as single-ingredient remedies derived from plants. It discusses the historical context of herbal medicine, referencing classical sources and outlining the evolution of herbal practices over the centuries. The author aims to clarify the chemical basis for the medicinal properties of common herbs, transitioning from anecdotal evidence to scientifically validated uses. Moreover, he underscores the resurgence of interest in herbal remedies by emphasizing their reliability as alternatives to synthesized medications in the waking age of modern science. (This is an automatically generated summary.)
Release date is 2006-09-22
Transcribed by Ruth Hart
Keywords: Botany, Medical